Predicting the rate effects on hooked-end fiber pullout performance from Ultra-High Performance Concrete (UHPC). (June 2019) - Cao, Y.Y.Y.; Yu, Q.L.; Brouwers, H.J.H.; Chen, W.
Abstract: The rate-dependent pullout performances of hooked-end fibers embedded in a UHPC matrix are investigated. Pullout load-slip relations corresponding to loading rates from 5 mm/min to 1000 mm/min and dynamic pullout responses are analyzed. The results show pullout energy is more rate sensitive than peak pullout load, e.g. with an embedded length of 15 mm, the dynamic increase factors (DIFs) under 1000 mm/min are 1.46 and 1.22, respectively. The rate effects on the pullout load are more prominent with a smaller embedded length due to the smaller concrete confinement, therefore the higher cracking potential. Further, a new analytical model to predict the dynamic peak pullout loads covering the loading rates from quasi-static to intermediate levels is proposed and validated. The present findings reveal that the inertial effects related to the crack initiation and propagation in the fiber-matrix interface have significant influences on the rate dependent pullout behaviors, which contribute to the potential utilization of UHPFRC composite in resisting dynamic loadings.